Draft Genome Sequence of Bacillus cereus TN10, a Chromium-Resistant and -Reducing Strain Isolated from Tannery Effluent - Hossain, Maqsud (Microbiol Resour Announc, 2020)
Here, we present the draft genome sequence of Bacillus cereus strain TN10, which exhibited chromium resistance and chromium-reducing ability. The whole-genome sequence analysis of strain TN10 will help us to understand its genetic factors involved in the bioremediation of Cr(6+).